KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA PADA PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) - Fahmi Rizqi Nashrullah; Mohammad Asikin; Budi Waluya; Zaenuri Zaenuri (Integral : Pendidikan Matematika, 2021)
Abstract It is important to develop mathematical critical thinking skills in students because they have an important role in understanding a problem. Mathematical critical thinking skills can be improved by learning Realistic Mathematics Education (RME) because learning prioritizes the process of mathematical modeling with students' environmental conditions as the basis of learning. This study aims to develop indicators of mathematical critical thinking skills and Realistic Mathematics Education (RME) learning steps that can foster students' mathematical critical thinking skills. The research method used in this study is the Systematic Literature Review (SLR) method. This method identifies, reviews, evaluates, and interprets existing research. Based on the literature review, developed several indicators of students' mathematical critical thinking skills, namely interpreting, analyzing, evaluating, drawing conclusions. In addition, developing several steps of Realistic Mathematics Education (RME) learning, namely preparation, opening, learning process, and closing. Keywords: Mathematical critical thinking skills, Realistic Mathematics Education, RME Abstrak Kemampuan berpikir kritis matematis penting dikembangkan pada diri siswa, karena memiliki peran penting dalam memahami suatu permasalahan. Kemampuan berpikir kritis matematis dapat ditingkatkan dengan pembelajaran Realistic Mathematics Education (RME) karena pembelajaran yang mengedepankan proses pemodelan matematika dengan kondisi lingkungan siswa sebagai dasar pembelajaran. Penelitian ini bertujuan mengembangkan indikator kemampuan berpikir kritis matematis dan langkah-langkah pembelajaran Realistic Mathematics Education (RME) yang dapat menumbuhkan kemampuan berpikir kritis matematis siswa. Metode penelitian yang digunakan pada penelitian ini adalah metode Systematic Literature Review (SLR). Dengan metode ini mengidentifikasi, mengkaji, mengevaluasi, dan menginterpretasikan penelitian yang ada. Berdasarkan kajian literatur, mengembangkan beberapa indikator kemampuan berpikir kritis matematis siswa, yaitu menginterpretasikan, menganalisis, mengevaluasi, menarik kesimpulan. Selain itu, mengembangkan beberapa langkah-langkah pembelajaran Realistic Mathematics Education (RME) yaitu persiapan, pembukaan, proses pembelajaran, dan penutup. Kata kunci: kemampuan berpikir kritis matematis, Realistic Mathematics Education, RME